Interplanetary File System for Custom Logging System Integrated with Smart Contract - Onesinus Saut Parulian; Irwansyah Saputra (Universitas Methodist Indonesia, 2025)
The agricultural sector faces challenges in managing dynamic data during transactions, particularly price quotations between farmers and buyers. Traditional smart contract systems often lack the flexibility to handle real-time data changes. This research proposes a customized logging system that integrates smart contracts with the InterPlanetary File System (IPFS) within a web application. By storing data references (hashes) on the blockchain and actual logs on IPFS, the system ensures reliable data recording, flexibility in updating transaction logs, and improved storage efficiency. This integration enhances the system's ability to manage fluctuating agricultural transactions. The proposed method aims to create a robust framework for managing price quotations, which can be extended to other industries with similar requirements.